Enhancement of Energy Storage Performance by Criticality in Lead‐Free Relaxor Ferroelectrics. Issue 7 (2nd May 2018) - Weyland, Florian; Zhang, Haibo; Novak, Nikola
Abstract : In modern electronic systems and energy conversion, efficient capacitors with large energy densities are needed. Relaxor ferroelectrics show the potential to achieve those requirements. The lead‐free relaxor ferroelectric 0.852(Na1/2 Bi1/2 TiO3 )–0.028(BaTiO3 )–0.12(K1/2 Bi1/2 TiO3 ) is investigated exhibiting the behavior of a wide range of Na1/2 Bi1/2 TiO3 ‐based relaxor systems. The criticality of this system is analyzed and a full electric field–temperature phase diagram is constructed. The energy storage performance is determined from polarization measurements in a wide temperature range. It is found that energy density and especially the efficiency is largely increased in the vicinity of the critical end point of the relaxor system. The concept of criticality is widely applicable to lead‐based and lead‐free relaxor ferroelectrics and therefore an important approach to increase energy storage performance in those systems. Abstract : Enhancing energy storage performance is crucial in ceramic capacitors for modern electronic systems and energy conversion. The temperature evolution from field‐induced first order to second order phase transition is analyzed and related to polarization properties. The criticality (CP) in a typical lead‐free relaxor ferroelectric is depicted and the relationship to enhanced recoverable energy density ( W rec ) and efficiency ( η ) is demonstrated.